The Inclusion of Ulema in the Aplication of Islam Nusantara Law for the Aceh Community - Muhammad Yusuf, Januddin; Yuslem, Nawir; Tanjung, Dhiauddin (Al-Risalah, 2023)
Islam Nusantara is recognized as an ideology that advocates the application of fiqh law while accommodating cultural and traditional values. In the contemporary evolution of religious comprehension, particularly in Aceh, the local community perceives cultural manifestations in worship as misguided. Therefore, the introduction of Islam Nusantara concept aims to rectify these misconceptions through cultural adjustment with Sharia, commonly referred to as Islamization. Considering these challenges, the role of ulemas should be examined by implementing and practicing fiqh law in the Aceh community. Furthermore, this study adopts qualitative and descriptive normative methods. Data are derived from a comprehensive literature review, interviews, and observations, and subjected to qualitative data analysis methods. The results show that fiqh practices in Aceh are always based on the fatwa of ulemas to provide legality of carrying out these practices. The inclusion of ulemas is indispensable to ensure the conformity of new cultural teachings with the established legal framework.